The Image of Lithuanian Public Prosecutors and Prosecutorial Offices - Valickas, Gintautas; Vanagaitė, Kristina (Teisė, 2022)
The article examines the character, similarities and differences of the image (or its separate components) of public prosecutors and prosecutorial offices perceived by the prosecutors (n = 322), police officers (n = 113), attorneys (n = 85), judges (n = 103) and the general public representing different age groups (n = 623), as well as the relations among the image of prosecutors and prosecutorial offices, experience accumulated by participants, and sociodemographic characteristics.
Keywords: image of public prosecutors and prosecutorial offices; components of the image; similarities and differences of the perceived image; elations among the image and socio-demographic characteristics